Detection of Uropathogenic Escherichia coli Virulence Factors’ fimH and fliC H7 in Urinary Tract Infections and Their Association with Antibiotics Resistance among Sudanese Children - Olla M. Siedahmed Osman; Ahmed Osman; Hind Mohamed Abushama (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
Background UTIs are one of the most common pathological conditions in both community and hospital settings. A broad spectrum of pathogens causes UTIs, it has been estimated that about 80% to 90% of cases worldwide develop UTI each year. However, the most frequent agent of community-acquired UTI is Uropathogenic Escherichia coli (UPEC), Some of UPEC genes have been associated with disease and antibiotic resistance. The presence of multidrug-resistant UPEC harboring several virulence factors, is a major risk factor for inpatients. This study aimed to detect the presence of virulence factors; fimH and fliC H7 genes and their possible association with antibiotic resistance, to evaluate the relation between virulence factors and antibiotic resistance among UPEC isolated from Sudanese symptomatic children’s patients with UTI, in Khartoum State- Sudan. Methods Sixty-six urine samples from study participants with symptomatic UTIs have been identified by clinician from two hospitals as UPEC using the conventional microbiological tests. All the isolates were subjected to antimicrobial sensitivity test using disk diffusion and polymerase chain reaction (PCR) assay to identify the presence of two putative virulence factors; fimH and fliC H7, and their association with antimicrobial resistance. Results Our results have shown that Amoxcacillin (penicillin group) was consistently the most resistance active (90.9%) of the systemically active antimicrobials, followed by Sulfamethoxazole (89.4%). On the other hand, sensitivity to nitrofurantoin (nitrofuran) was found to be the highest (89.4%). FimH gene has the highest prevalence among E. coli isolates (63.6%), followed by fliC gene (53.0%). A statistically significant association was found between the presence of fimH gene and resistance of E. coli to Polynaphethol with Chi-square p-value = 0.016 and odds ratio =5.353. Another significant association was found with resistance of E. coli to Chloramphenicol (Chi-Square p-value = 0.038, odds ratio = 3.103) and presence of fimH gene, also there was a significant association between the presence of fliC H7 gene and resistance of E. coli to Cephalexin with a (Chi-Square p-value = 0.001 and odds ratio = 5.869) Conclusions The study highlighted the prevalence of UPEC isolates which harbored the virulence factors and their association with antibiotic resistance which possibly cause the urine disease. The outcome of the study may represent targets for improving the regimen used and therapeutics against UPEC in Sudan.